PEMENUHAN HAK PENDIDIKAN TERHADAP PENYANDANG DISABILITAS DI KOTA BENGKULU - Pipi Susanti; Ari Wirya Dinata; Arie Elca Putra (Esensi Hukum, 2024)
In Indonesia, most people with disabilities live in vulnerable conditions. Persons with equal rights and opportunities to obtain a life that is prosperous, independent, and without discrimination, are required to have laws and regulations that can guarantee their implementation. Article 31 paragraph (1) of the 1945 Constitution of the Republic of Indonesia regulates that the right to education is a guaranteed human right. In practice, children with disabilities are very vulnerable to discriminatory treatment in obtaining their rights, especially the right to education. This is caused by the unequal physical or psychological conditions of children with disabilities. The conditions of people with disabilities vary, some have mental disabilities, physical disabilities, and a combination of mental and physical disabilities. In Bengkulu City, not all of the children with disabilities were able to receive education. Of the total, only half of the children were able to experience education services. This discourse questions about how the Bengkulu city government fulfills the right to education for children with disabilities, what are the obstacles faced by the government in fulfilling the education rights for children with disabilities. This paper presents the discourse by explaining it from a juridical-empirical perspective using a legal and social science approach. Where field studies will be carried out by conducting interviews. The right to education for persons with disabilities as contained in Article 10 of Law No. 8 of 2016 concerning Persons with Disabilities. In fulfilling the rights of children with disabilities, the Bengkulu city government provides assistance through a disability forum provided by the ministry managed by the social service where assistance is provided for nutrition and for child therapy which has been given for 3 consecutive years. Assistance provided by local governments to fulfill the rights of children with disabilities is hearing aids, rice and cash. The obstacles faced by the Bengkulu city government in fulfilling the rights of persons with disabilities are the lack of coordination between the provincial and city governments in fulfilling the rights of children with disabilities, school infrastructure facilities that are still not friendly to children with disabilities, buildings that are not yet feasible.